2015
DOI: 10.1039/c5ra02339d
|View full text |Cite
|
Sign up to set email alerts
|

One pot oxidative cleavage of cyclohexene to adipic acid using silver tungstate nano-rods in a Brønsted acidic ionic liquid

Abstract: The first catalytic application of silver tungstate is disclosed for the synthesis of adipic acid from the oxidative cleavage of cyclohexene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…Silver tungstate (Ag 2 WO 4 )-based materials constitute a particularly intensively researched family of inorganic compounds because of their particular crystal and electronic structures. [8][9][10][11][12] In response to their extensive range of innovative properties and practical applications, a plethora of experimental works have been published on the synthesis and properties of Ag 2 WO 4 -based materials, [13][14][15][16][17][18][19][20][21][22][23][24][25][26] and on their applications in photocatalysis, 17,19,20,25 catalysis, 14,18 photoluminescence, 9,13,15 sensors, 22 and as antibacterial agents. 21,23,26 Ag 2 WO 4 exhibits stunningly complex polymorphism, 27 and its understanding has evoked recent interest due to both fundamental scientic and technological aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Silver tungstate (Ag 2 WO 4 )-based materials constitute a particularly intensively researched family of inorganic compounds because of their particular crystal and electronic structures. [8][9][10][11][12] In response to their extensive range of innovative properties and practical applications, a plethora of experimental works have been published on the synthesis and properties of Ag 2 WO 4 -based materials, [13][14][15][16][17][18][19][20][21][22][23][24][25][26] and on their applications in photocatalysis, 17,19,20,25 catalysis, 14,18 photoluminescence, 9,13,15 sensors, 22 and as antibacterial agents. 21,23,26 Ag 2 WO 4 exhibits stunningly complex polymorphism, 27 and its understanding has evoked recent interest due to both fundamental scientic and technological aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Silver tungstate, α‐Ag 2 WO 4 , is a material that has received special attention from the scientific community because of its applications in a variety of fields such as photoluminescence, bactericide behavior, gas sensor, and photocatalytic activity …”
Section: Introductionmentioning
confidence: 99%
“…Primarily, this is because these phenomena occur too rapidly to be detected on the nanocrystal surfaces. Very recently, using an electron beam in an electron microscope under high vacuum, we identified the formation and growth of Ag nanoparticles on α-Ag 2 WO 4 [51][52][53][54][55][56][57] [61], and other authors have also reported interest in these fascinating systems [62][63][64][65][66][67][68][69][70][71]. Much of the applications of the aforementioned Ag materials are based on their photoluminescence properties [51] and bactericidal/antibacterial effect (which allows their use in clinical sterilization) [55].…”
Section: Introductionmentioning
confidence: 99%